Trends in the Prevalence and Incidence of Psoriasis and Psoriatic Arthritis in Ontario, Canada: A Population‐Based Study. Issue 8 (11th July 2019) - Eder, Lihi; Widdifield, Jessica; Rosen, Cheryl F.; Cook, Richard; Lee, Ker‐Ai; Alhusayen, Raed; Paterson, Michael J.; Cheng, Stephanie Y.; Jabbari, Shirin; Campbell, Willemina; Bernatsky, Sasha; Gladman, Dafna D.; et al.
Abstract : Objective: To estimate the prevalence and incidence of psoriasis and psoriatic arthritis (PsA) over time in Ontario, Canada. Methods: We performed a population‐based study of Ontario health administrative data, using validated case definitions for psoriasis and PsA. We computed the crude and age‐ and sex‐standardized cumulative prevalence and incidence of psoriasis from 2000 to 2015. Results: Among the 10, 774, 802 individuals ages ≥20 years residing in Ontario in 2015, we identified 273, 238 patients with psoriasis and 18, 655 patients with PsA, equating to cumulative prevalence estimates of 2.54% and 0.17%, respectively. Correcting the prevalence estimates for imperfect sensitivity and specificity resulted in similar estimates. The male:female ratio was approximately 1.0 for both conditions. For psoriasis, the age‐ and sex‐standardized cumulative prevalence increased from 1.74% in 2000 to 2.32% in 2015. For PsA, the age‐ and sex‐standardized cumulative prevalence increased from 0.09% in 2008 to 0.15% in 2015. Between 2008 and 2015, annual incidence rates for psoriasis decreased, whereas those for PsA remained relatively stable. Conclusion: The prevalence and incidence of psoriasis and PsA in Ontario are similar to those observed in Europe and the US. The steady increase in the prevalence of psoriasis and PsA over the past decade may be due to a combination of population aging, population growth, and increasing life expectancy.